'A University is a society': an environmental history of the METU 'campus'. Issue 4 (18th May 2016) - Sargın, Güven Arif; Savaş, Ayşen
Abstract : The formation of a 'society' was the major goal of the founders of the Middle East Technical University (METU) in Turkey, which was established in 1956 and became a significant source of intellectual, ideological and architectural capital for its region. The university was designed as a total entity, a three-dimensional modern grid spread over the barren Anatolian prairie, and, in half a century, succeeded in transforming its immediate environment into an 'ideal landscape'. There has been no publication to date documenting the formation processes of the institution, nor its impact as an environmental revolution. In opposition to the consensus that the development of this university was rooted in the United Nation's programmes for higher education in the developing world and the United States' post-war policy in the region, this paper suggests that the METU Project was rather indicative of the Turkish Republic's desire for modernisation in all of its social and ideological programmes. This paper examines the METU Project in a bid to understand how the Anatolian prairie was transformed into an urban environment, and the unique ways it is perceived in the surrounding political contexts of institutional and everyday life. By compiling an environmental historiography, the intention is to find answers to the questions of how, and to what extent, the ideal landscape was influential, and how it was presented with architecture through social and political practices.